Monolithic catalyst as well as preparation method and application thereof
By attaching a coating of titanium silicon molecular sieve and metal oxide on the support and dispersing precious metal components, the existing catalysts have been solved, and the effect of efficient catalytic oxidation of carbon-based oxygen-containing molecular gases is achieved.
Patent Information
- Application Number
- CN202311166887.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-11
AI Technical Summary
In the process of catalyzing carbon-based oxygen-containing molecular gases, existing catalysts have problems such as poor shape selection, low selectivity and poor activity, and are highly prepared and complex in the process of catalyzing carbon-based oxygen-containing molecular gases.
The coating structure is regulated to improve the construction of catalytic active sites by attaching a coating containing titanium silicon molecular sieve and metal oxide to the support and dispersing precious metal components in the coating.
The efficient catalytic oxidation efficiency of the catalyst is achieved, the content of precious metal catalysts is reduced, the adsorption capacity of carbon-based oxygen-containing molecular gases and oxygen is increased, and the stability and adaptability of the catalyst are improved.
Smart Images

Figure CN119588413A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and specifically to an integral catalyst and a preparation method and application thereof, and more specifically to an integral catalyst for catalytic oxidation of carbon-based oxygen-containing molecular gases and a preparation method thereof and application thereof in catalytic oxidation of carbon-based oxygen-containing molecular gases. Background Art
[0002] Carbon monoxide (CO) is a colorless, odorless, toxic gas that generally comes from incomplete combustion or partial oxidation of coal, gasoline and natural gas. CO has a strong binding force with hemoglobin and is therefore highly toxic. At higher concentrations, it can cause varying degrees of poisoning symptoms in people, harming the brain, heart, liver, kidney, lungs and other tissues of the human body, and even electric shock-like death. The minimum lethal concentration for human inhalation is 5000ppm (5 minutes). Therefore, in the production process of petrochemical products, strict requirements should be made for the emission content of CO in tail gas. With increasingly stringent environmental protection requirements, Beijing, Zibo and other regions have strictly restricted the CO concentration in the tail gas of chemical plants.
[0003] In some chemical production processes, the tail gas produced contains low concentrations of CO gas (<20000ppm) (such as the analytical gas and CO2 product gas of the low-temperature methanol washing device used for acid gas removal in the coal gasification unit). For this type of tail gas, the recovery cost is relatively high. In order to meet the emission requirements, adsorption, photocatalysis, low-temperature plasma conversion, combustion and other methods are usually used to remove CO. Among them, the catalytic oxidation method introduces a high-efficiency catalyst on the basis of the combustion method to reduce the temperature of the combustion process. It has the advantages of simple process and high removal efficiency, and therefore has received widespread attention. In the petrochemical production process, carbon-based energy small molecules often undergo incomplete reactions during the directed oxidation process, resulting in the enrichment of oxygen-containing small molecule gases in the exhaust gas or circulating carrier gas of the device, resulting in not only the risk of combustion and explosion in the chemical production process, but also the formation of photochemical phenomena, causing pollution to the surrounding environment. At present, the main method for treating the oxygen-containing small molecule tail gas discharged from the oxidation process of petrochemical plants is catalytic oxidation. The catalytic oxidation method can completely oxidize the oxygen-containing small molecule gas to form carbon dioxide. At the same time, in order to meet the requirements of low pressure drop and large air volume conditions, the current catalytic oxidation method generally uses a monolithic catalyst loaded with precious metals. However, the pore distribution of the coating matrix is uneven and cannot be controlled, resulting in poor catalyst shape selectivity, low selectivity, and poor activity.
[0004] Patent application CN102689911A uses microwave alkali treatment to corrode nano-scale ZSM-5 molecular sieves to prepare multi-level pore ZSM-5 molecular sieve nanospheres with adjustable pore size between 30-150nm. However, these preparation methods of multi-level pore molecular sieves have the problems of high preparation cost and complicated process, which is not conducive to large-scale production.
[0005] Patent application CN107720771A discloses a method for preparing a macroporous-microporous molecular sieve catalyst TS-1, which uses mesoporous silica microspheres as hard templates and silicon sources, and controls the reaction temperature, reaction time, and the amount of structure-directing agent to synthesize a macroporous-microporous molecular sieve catalyst with adjustable macropore diameter. However, the preparation of the molecular sieve only introduces the macropore diameter, and does not achieve adjustable diameter, making it difficult to flexibly adapt to the ever-changing raw material requirements.
[0006] Patent application CN111408342A discloses a high-silicon composite molecular sieve adsorbent for VOCs removal and its preparation method. This method performs hydrothermal crystallization under microwave conditions, regulates the surface hydrophobicity of the molecular sieve pores, but does not change the pore structure and size, and cannot fully utilize its shape-selective catalytic ability.
[0007] Therefore, the development of catalysts with adjustable pores, high efficiency, low cost, environmental friendliness, and long-lasting strength has become a research hotspot and application trend of catalytic oxidation catalysts at home and abroad. Summary of the invention
[0008] The purpose of the present invention is to provide an integral catalyst and its preparation method and application for an efficient removal process of carbon-based oxygen-containing molecular gases (such as CO, VOCs, etc.) in exhaust gas discharged from a chemical production process. In the present invention, the coating structure of the integral catalyst is regulated to promote the dispersion of active precious metals and the exposure of active phases, efficiently construct catalytic active sites on the catalyst surface, reduce the content of precious metal catalysts, increase the adsorption capacity of carbon-based oxygen-containing molecular gases and oxygen, promote the adsorption and activation of oxygen, and thus improve the catalytic efficiency of the catalyst.
[0009] In order to achieve the above object, the present invention provides a monolithic catalyst on one hand, the monolithic catalyst comprising:
[0010] A carrier, wherein the carrier is a regular carrier treated with acid;
[0011] a coating layer attached to the carrier, the coating layer comprising titanium silicon molecular sieve and metal oxide; and
[0012] an active component dispersed in the coating, the active component comprising a noble metal and optionally an alloying metal;
[0013] The powder loss rate of the coating is less than 1%, preferably 0.1-1%; the particle size of the active component is 2-3nm.
[0014] Preferably, the particle size of the coating is 50-500 nm.
[0015] Preferably, the mesoporous channel size of the coating is 1-50 nm, and the specific surface area is 300-600 m2 / g.
[0016] Preferably, relative to 100 parts by weight of the carrier, the content of the coating layer is 1-10 parts by weight, and the content of the active component is 0.1-1 part by weight.
[0017] Preferably, the structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
[0018] Preferably, in the coating, the weight ratio of the titanium silicon molecular sieve to the metal oxide is 1:0.1-0.5.
[0019] Preferably, the titanium silicate molecular sieve is TS-1 molecular sieve.
[0020] Preferably, the metal oxide is selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2.
[0021] Preferably, in the active component, the molar ratio of the noble metal to the alloy metal is 1:0.1-0.3.
[0022] Preferably, the noble metal is at least one of silver, ruthenium, rhodium, palladium, osmium, iridium and platinum, more preferably a combination of platinum and palladium.
[0023] Preferably, the alloy metal is at least one of Fe, La and Ce, more preferably a combination of La and Ce.
[0024] The second aspect of the present invention provides a method for preparing a monolithic catalyst, the method comprising the following steps:
[0025] (1) treating the structured support with acid;
[0026] (2) mixing an alcohol solution of a titanium source with an aqueous solution containing a microporous template and a silicon source, aging, removing alcohol, and then mixing the obtained gel solution with titanium silicon molecular sieve seed crystals and a mesoporous template;
[0027] (3) mixing the mixed solution obtained in step (2) with the metal oxide and ball milling to obtain a coating slurry;
[0028] (4) The coating slurry is mixed with a mixed solution containing a noble metal precursor and an optional structural additive, and the obtained mixed slurry is added to the acid-treated structured support, followed by purging, drying, calcining and reducing in sequence.
[0029] Preferably, in step (1), the acid treatment process comprises: subjecting the structured carrier to a reflux treatment with an acidic solution, and then washing it to neutrality and drying it.
[0030] Preferably, the concentration of the acidic solution is 1-3 mol / L.
[0031] Preferably, the acid in the acidic solution is at least one of nitric acid, sulfuric acid and hydrochloric acid.
[0032] Preferably, the reflux treatment conditions include: a temperature of 70-90° C. and a time of 12-36 hours.
[0033] Preferably, the structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
[0034] Preferably, in step (2), the specific process of mixing the alcohol solution of the titanium source with the aqueous solution containing the microporous template and the silicon source is: adding the alcohol solution of the titanium source to the aqueous solution containing the microporous template and the silicon source at a rate of 0.005-0.015 mL / min, and stirring and mixing for 2-5 hours.
[0035] Preferably, the titanium source is selected from at least one of tetraalkoxytitanium, tetraalkyl titanate and titanium tetrachloride.
[0036] Preferably, the microporous template is selected from at least one of tetrapropylammonium hydroxide, tetrapropylammonium bromide and tetraethylammonium hydroxide.
[0037] Preferably, the silicon source is selected from at least one of silicates, silicic acid, silica hydrogel and tetraethyl orthosilicate.
[0038] Preferably, the titanium silicon molecular sieve seed crystals are TS-1 molecular sieve seed crystals.
[0039] Preferably, the mesoporous template agent is selected from at least one of P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer), CTAB (hexadecyltrimethylammonium bromide) and n-butylamine.
[0040] Preferably, in step (3), the metal oxide is selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2.
[0041] Preferably, in step (4), the pH value of the mixed solution containing the noble metal precursor and the structural additive is 9-12.
[0042] Preferably, the noble metal precursor is selected from at least one of chloroplatinic acid, 2-hydroxyethylamine hexahydroxoplatinic acid (IV), platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate.
[0043] Preferably, the structural additive is selected from at least one of ferric nitrate, cerium nitrate, lanthanum nitrate, lanthanum sulfate, lanthanum chloride, cerium sulfate and cerium trioxide.
[0044] Preferably, in step (4), the purging process is performed by using an air knife purging at 1.5-2.5 MPa.
[0045] Preferably, the calcination conditions include: a temperature of 200-300° C. and a time of 4-10 hours.
[0046] Preferably, during the reduction process, the reducing atmosphere is H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, and a mixed atmosphere of different CO concentrations.
[0047] Preferably, the reduction conditions include: catalyst heating rate of 2-20°C / min, reduction temperature of 300-450°C, and reduction time of 1-10h.
[0048] The third aspect of the present invention provides a monolithic catalyst prepared by the above method.
[0049] A fourth aspect of the present invention provides the use of the above-mentioned integral catalyst in catalytic oxidation of carbon-based oxygen-containing molecular gases.
[0050] According to the technical solution of the present invention, in the process of preparing the catalyst, the structured carrier is treated with acid and then a coating slurry containing titanium silicon molecular sieve is attached. The titanium silicon molecular sieve in the coating slurry can react with the exposed hydroxyl groups on the surface of the structured carrier after the acid treatment, and a chemical bond is formed between the coating and the structured carrier, so that the coating has high firmness and extremely low powder loss rate; and the technical solution of the present invention can regulate the pores of the coating matrix, thereby realizing the regulation of the coating structure of the integral catalyst, promoting the dispersion of active precious metals and the exposure of active phases, efficiently constructing catalytic active sites on the catalyst surface, reducing the content of precious metal catalysts, and increasing the adsorption capacity of carbon-based oxygen-containing molecular gases and oxygen, promoting the adsorption and activation of oxygen, and thereby improving the catalytic efficiency of the catalyst.
[0051] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0052] (1) The monolithic catalyst prepared by the present invention has high oxygen adsorption and activation capabilities and high catalytic oxidation efficiency;
[0053] (2) The monolithic catalyst prepared by the present invention has high mechanical strength and is suitable for high space velocity and large volume gas treatment conditions;
[0054] (3) In the monolithic catalyst of the present invention, the pore structure of the coating matrix is adjustable, which has the advantages of strong quantitative adjustability and strong raw material adaptability;
[0055] (4) In the monolithic catalyst of the present invention, the catalyst coating and the carrier are bonded by chemical bonds, which has the advantages of high firmness, strong water resistance, and is conducive to continuous long-term operation;
[0056] (5) In the monolithic catalyst of the present invention, the content of active precious metal components is relatively low, which can greatly reduce the operating cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 is a SEM image of the monolithic catalyst prepared in Example 1;
[0058] Figure 2 This is a TEM image of the monolithic catalyst prepared in Example 1. DETAILED DESCRIPTION
[0059] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0060] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0061] In the present invention, unless otherwise specified, the concentration "%" of a gas refers to "volume %"; the "space velocity" refers to "volume space velocity"; and the pressure refers to absolute pressure.
[0062] The monolithic catalyst of the present invention comprises:
[0063] A carrier, wherein the carrier is a regular carrier treated with acid;
[0064] a coating layer attached to the carrier, the coating layer comprising titanium silicon molecular sieve and metal oxide; and
[0065] An active component is dispersed in the coating, the active component comprising a noble metal and optionally an alloying metal.
[0066] In the monolithic catalyst described in the present invention, the titanium silicon molecular sieve in the coating has a strong bonding strength with the regular carrier, and the powder loss rate of the coating is low. Specifically, the powder loss rate of the coating is less than 1%, preferably 0.1-1%, and more preferably 0.1-0.5%. In the present invention, the powder loss rate is detected by ultrasonic oscillation method, and the detection conditions include: ultrasonic frequency 45kHz, ultrasonic power 130W, and treatment time 60min.
[0067] In the monolithic catalyst of the present invention, the active component is fully dispersed in the coating layer, and the particle size of the active component is relatively small. Specifically, the particle size of the active component is 1-8 nm, preferably 2-6 nm, and more preferably 2-3 nm.
[0068] In the monolithic catalyst of the present invention, the particle size of the coating layer may be 50-500 nm, preferably 80-480 nm.
[0069] In the monolithic catalyst of the present invention, the mesopore size of the coating may be 1-50 nm, preferably 1.7-45 nm; the specific surface area may be 300-600 m 2 / g, preferably 400-550m 2 / g.
[0070] In the monolithic catalyst described in the present invention, the content of the coating layer can be 1-10 parts by weight, specifically, for example, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight or 10 parts by weight, relative to 100 parts by weight of the carrier; the content of the active component can be 0.1-1 part by weight, specifically, for example, 0.1 part by weight, 0.2 part by weight, 0.3 part by weight, 0.4 part by weight, 0.5 part by weight, 0.6 part by weight, 0.7 part by weight, 0.8 part by weight, 0.9 part by weight or 1 part by weight.
[0071] In the present invention, the structured carrier is preferably selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier, and the most preferred one is a cordierite honeycomb carrier.
[0072] In the monolithic catalyst of the present invention, in the coating layer, the weight ratio of the titanium silicon molecular sieve to the metal oxide may be 1:0.1-0.5, preferably 1:0.2-0.4.
[0073] In the monolithic catalyst of the present invention, the titanium silicalite molecular sieve forming the coating layer can be any conventional mesoporous titanium silicalite molecular sieve. In the most preferred embodiment, the titanium silicalite molecular sieve is TS-1 molecular sieve.
[0074] In the monolithic catalyst of the present invention, in the coating layer, the metal oxide may be selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2.
[0075] In the monolithic catalyst of the present invention, in the active component, the alloy metal is an optional component. In a more preferred embodiment, the active component contains a noble metal and an alloy metal. In this preferred embodiment, the active component exists in the form of a noble metal element, an alloy, and a noble metal oxide. In the active component, the molar ratio of the noble metal to the alloy metal can be 1:0.1-0.3, preferably 1:0.15-0.2.
[0076] In the monolithic catalyst of the present invention, in the active component, the noble metal can be selected from at least one of ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably a combination of platinum and palladium. When the noble metal is a combination of platinum and palladium, the molar ratio of platinum to palladium can be 1:0.5-2, and most preferably 1:1.
[0077] In the monolithic catalyst of the present invention, in the active component, the alloy metal may be at least one of Fe, La and Ce, preferably a combination of La and Ce. When the alloy metal is a combination of La and Ce, the molar ratio of La to Ce may be 1:0.5-2, and most preferably 1:1.
[0078] The method for preparing the monolithic catalyst of the present invention comprises the following steps:
[0079] (1) treating the structured support with acid;
[0080] (2) mixing an alcohol solution of a titanium source with an aqueous solution containing a microporous template and a silicon source, aging, removing alcohol, and then mixing the obtained gel solution with titanium silicon molecular sieve seed crystals and a mesoporous template;
[0081] (3) mixing the mixed solution obtained in step (2) with the metal oxide and ball milling to obtain a coating slurry;
[0082] (4) The coating slurry is mixed with a mixed solution containing a noble metal precursor and an optional structural additive, and the obtained mixed slurry is added to the acid-treated structured support, followed by purging, drying, calcining and reducing in sequence.
[0083] In step (1), the acid treatment process can remove impurities contained in the structured support and form a bare hydroxyl surface. The acid treatment process can include: refluxing the structured support with an acidic solution, then washing to neutrality and drying.
[0084] Specifically, the concentration of the acidic solution may be 1-3 mol / L, preferably 1.5-2.5 mol / L, and most preferably 2 mol / L.
[0085] Specifically, the acid in the acidic solution may be an inorganic strong acid, preferably at least one of nitric acid, sulfuric acid and hydrochloric acid, and most preferably nitric acid.
[0086] Specifically, the reflux treatment conditions may include: a temperature of 70-90° C., preferably 80° C.; and a time of 12-36 hours, preferably 24 hours.
[0087] In the method described in the present invention, the regular carrier can be selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier, preferably a cordierite honeycomb carrier.
[0088] In step (2), the specific process of mixing the alcohol solution of the titanium source with the aqueous solution containing the microporous template and the silicon source is: adding the alcohol solution of the titanium source to the aqueous solution containing the microporous template and the silicon source at a rate of 0.005-0.015 mL / min, and stirring and mixing for 2-5 hours.
[0089] In the present invention, the titanium source can be selected from water-soluble or water-soluble titanium-containing compounds, generally referring to titanium dioxide (TiO2) sources. In a specific embodiment, the titanium source includes but is not limited to at least one of tetraalkoxy titanium, tetraalkyl titanate and titanium tetrachloride, and n-butyl titanate is most preferred.
[0090] In the present invention, in the alcohol solution of the titanium source, the alcohol solvent used may be at least one of isopropanol, ethanol and n-propanol.
[0091] In the present invention, the concentration of the alcohol solution of the titanium source may be 5-15% by weight.
[0092] In the present invention, the silicon source can be selected from water-soluble or water-soluble silicon-containing compounds, generally referring to a silicon dioxide (SiO2) source. In a specific embodiment, the silicon source includes but is not limited to at least one of silicate, silicic acid, silica hydrogel and tetraethyl orthosilicate, preferably tetraethyl orthosilicate.
[0093] In the present invention, the microporous template agent may be at least one selected from tetrapropylammonium hydroxide, tetrapropylammonium bromide and tetraethylammonium hydroxide.
[0094] In the present invention, the titanium silicate molecular sieve seed crystal is preferably a TS-1 molecular sieve seed crystal.
[0095] In the present invention, the mesoporous template agent may be selected from at least one of P123, CTAB and n-butylamine.
[0096] In step (2), the aging process can be carried out at room temperature for 2-5 hours.
[0097] In step (2), the alcohol removal process is specifically as follows: heating the aged mixed solution to 85-95°C at a rate of 1-20°C / min (preferably 5-17°C / min), and removing alcohol at 85-95°C for 10-15 hours.
[0098] In step (2), the process of mixing the gel solution with the titanium silicalite seed crystals and the mesoporous template is carried out under stirring. The mixing conditions may include: a temperature of 35-45° C. and a time of 0.5-2 hours.
[0099] In step (3), the metal oxide may be selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2.
[0100] In step (3), the mixing ball milling time can be 1-5 hours, preferably 2-3 hours.
[0101] In step (4), the coating slurry is mixed with a mixed solution containing a noble metal precursor and a structural additive under stirring. The mixing conditions may include: a temperature of 15-40° C., preferably 25° C.; and a time of 1-4 hours, preferably 3 hours.
[0102] In step (4), the pH value of the mixed solution containing the noble metal precursor and the structural additive is 9-12. Specifically, the pH value of the mixed solution can be 9, 10, 11 or 12, for example.
[0103] In the present invention, the noble metal in the noble metal precursor is at least one of silver, ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably a combination of platinum and palladium. In a specific embodiment, the noble metal precursor is at least one of chloroplatinic acid, hexahydrooxoplatinic acid (IV) 2-hydroxyethylamine salt, platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate.
[0104] In step (4), the structural additive is added to provide alloy metals so that the active components in the prepared monolithic catalyst exist in the form of noble metal elements, alloys and noble metal oxides. In a specific embodiment, the structural additive is selected from at least one of ferric nitrate, cerium nitrate, lanthanum nitrate, lanthanum sulfate, lanthanum chloride, cerium sulfate and cerium trioxide.
[0105] In step (4), the purging process may be performed by using an air knife purging at 1.5-2.5 MPa.
[0106] In step (4), the drying process can be carried out in a drying oven. Specifically, the temperature of the drying oven can be 80-120° C., preferably 100° C.; the drying time can be 5-24 hours, preferably 12 hours.
[0107] In step (4), the calcination conditions may include: a temperature of 200-300° C. and a time of 4-10 hours.
[0108] In step (4), during the reduction process, the reducing atmosphere may be H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, and a mixed atmosphere of different CO concentrations. In a specific embodiment, the reducing atmosphere is a mixed atmosphere of different H2 concentrations and / or a mixed atmosphere of different CO concentrations, and the formation of surface oxygen vacancies of the catalyst is efficiently controlled by regulating the reducing atmosphere. Specifically, the reducing atmosphere may be, for example, 5% H2 (N2 dilution), 10% H2 (N2 dilution), 15% H2 (N2 dilution), 5% CO (N2 dilution), etc.
[0109] In step (4), the reduction conditions may include: a catalyst heating rate of 2-20° C. / min, a reduction temperature of 300-450° C., and a reduction time of 1-10 h.
[0110] In the method described in the present invention, the amounts of various reaction raw materials used in steps (1) to (4) are such that in the prepared integral catalyst, the content of the coating is 1-10 parts by weight, preferably 2-8 parts by weight, relative to 100 parts by weight of the carrier; and the content of the active component is 0.1-1 part by weight, preferably 0.1-0.5 part by weight.
[0111] The present invention also provides a monolithic catalyst prepared by the above method. In the monolithic catalyst, the titanium silicon molecular sieve in the coating reacts with the exposed hydroxyl groups on the surface of the regular carrier after acid treatment to form a chemical bond, so that the coating has high firmness and extremely low powder loss rate; moreover, the active precious metal is evenly dispersed and the particle size of the active component is small.
[0112] The present invention also provides the use of the above-mentioned integral catalyst in catalytic oxidation of carbon-based oxygen-containing molecular gas.
[0113] The following examples further illustrate the monolithic catalyst and its preparation method and application of the present invention. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.
[0114] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0115] Example 1
[0116] This example is used to illustrate the monolithic catalyst and its preparation method and application according to the present invention.
[0117] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0118] Secondly, 3.6g of isopropanol and 0.368g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01ml / min and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 1g of commercially available TS-1 seed crystals and 0.5g of P123 at 40°C for 1h to obtain solution 5, 5ml of 1mol / L CTAB was added to solution 5, mixed and stirred for 2h, and then 0.35g of metal oxide TiO2 was added, mixed and ball-milled for 2h to obtain coating slurry 6.
[0119] Then, 0.5L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 200ml of 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) were stirred at 25°C and pH 9 for 3h to obtain solution 7. Solution 7 was added to the coating slurry 6 and stirred for 30min to obtain mixed slurry 8. Then, the mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain the monolithic catalyst Cat-1. The content of active precious metal components is 0.15% by weight, the particle size of active precious metal components is between 2.1-2.2nm, the particle size of coating is between 80-150nm, the mesopore size distribution is 2-5nm, and the specific surface area is about 400m 2 / g, and the powder loss rate of the coating is 0.2%.
[0120] The SEM and TEM images of the monolithic catalyst are shown in Figure 2. Figure 1 and Figure 2 shown.
[0121] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 265℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0122] Example 2
[0123] This example is used to illustrate the monolithic catalyst and its preparation method and application according to the present invention.
[0124] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 1.5 mol / L sulfuric acid at 70° C. reflux for 36 h, washed with deionized water to a pH value of 7, and dried naturally for later use.
[0125] Secondly, 3.6g of isopropanol and 0.368g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.005ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 4 hours, and then heated to 90°C at a heating rate of 10-12°C / min, and alcohol was removed at 90°C for 10 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 2g of commercially available TS-1 seeds and 0.5g of P123 at 40°C for 1h to obtain solution 5, 5ml of 3mol / L CTAB was added to solution 5, mixed and stirred for 2h, and then 0.35g of metal oxide Al2O3 was added, mixed and ball-milled for 2h to obtain coating slurry 6.
[0126] Then, 0.5L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 200ml of 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) were stirred at 20°C and pH 10 for 4h to obtain solution 7. Solution 7 was added to the coating slurry 6 and stirred for 30min to obtain mixed slurry 8. Then, the mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2.5MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 230°C for 8 hours. Then, it was reduced at 380°C (heating rate of 8°C / min) for 6 hours in a 5% CO, 95% N2 atmosphere to obtain the monolithic catalyst Cat-2. The content of active precious metal components is 0.16% by weight, the particle size of active precious metal components is between 2.3-2.5nm, the particle size of coating is between 150-200nm, the mesopore size distribution is 8-12nm, and the specific surface area is about 380m 2 / g, and the powder loss rate of the coating is 0.2%.
[0127] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 275℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0128] Example 3
[0129] This example is used to illustrate the monolithic catalyst and its preparation method and application according to the present invention.
[0130] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2.5 mol / L hydrochloric acid at 90° C. reflux for 12 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0131] Secondly, 3.6g of isopropanol and 0.368g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.015ml / min and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 2 hours, then heated to 90°C at a heating rate of 14-15°C / min, and alcohol was removed at 90°C for 14 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 1g of commercially available TS-1 seed crystals and 1g of P123 at 40°C for 1h to obtain solution 5, 5ml of 5mol / L CTAB was added to solution 5, mixed and stirred for 2h, and then 0.35g of metal oxide ZrO2 was added, mixed and ball-milled for 2h to obtain coating slurry 6.
[0132] Then, 0.5L of 1mol / L chloroplatinic acid and palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 200ml of 1mol / L cerium nitrate and lanthanum nitrate mixed solution (molar ratio of cerium to lanthanum is 1:1) were stirred at 30°C and pH 11 for 2h to obtain solution 7. Solution 7 was added to the coating slurry 6 and stirred for 30min to obtain mixed slurry 8. Then, the mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 1.5MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 270°C for 5 hours. Then, it was reduced at 420°C (heating rate of 12°C / min) for 4 hours in an atmosphere of 15% H2 and 85% N2 to obtain a monolithic catalyst Cat-3. The content of active precious metal components is 0.15% by weight, the particle size of active precious metal components is between 2.0-2.1nm, the particle size of coating is between 50-100nm, the mesopore size distribution is 3-4nm, and the specific surface area is about 480m 2 / g, and the powder loss rate of the coating is 0.2%.
[0133] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1, reaction pressure 0.1MPa, reaction temperature 245℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0134] Example 4
[0135] This example is used to illustrate the monolithic catalyst and its preparation method and application according to the present invention.
[0136] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0137] Secondly, 3.6g of isopropanol and 0.368g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.008ml / min and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 1g of commercially available TS-1 seed crystals and 0.5g of P123 at 40°C for 1h to obtain solution 5, 10ml of 1mol / L CTAB was added to solution 5, mixed and stirred for 2h, and then 0.35g of metal oxide TiO2 was added, mixed and ball-milled for 2h to obtain coating slurry 6.
[0138] Then, 0.6L of 1mol / L chloroplatinic acid and palladium chloride mixed solution (molar ratio of platinum to palladium is 1.5:1) and 240ml of 1mol / L cerium nitrate and lanthanum nitrate mixed solution (molar ratio of cerium to lanthanum is 1:1) were stirred for 3h at 25°C and pH 10 to obtain solution 7. Solution 7 was added to the coating slurry 6 and stirred for 30min to obtain mixed slurry 8. Then, the mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 200°C for 10 hours. Then, it was reduced at 420°C (heating rate of 8°C / min) for 6 hours in a 10% H2, 90% N2 atmosphere to obtain the monolithic catalyst Cat-4. The content of active precious metal components is 0.18% by weight, the particle size of active precious metal components is between 2.1-2.2nm, the particle size of coating is between 100-150nm, the mesopore size distribution is 18-22nm, and the specific surface area is about 400m2 / g, and the powder loss rate of the coating is 0.2%.
[0139] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 275℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0140] Example 5
[0141] This example is used to illustrate the monolithic catalyst and its preparation method and application according to the present invention.
[0142] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0143] Secondly, 3.6g of isopropanol and 0.368g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.005ml / min and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 1g of commercially available TS-1 seed crystals and 0.5g of P123 at 40°C for 1h to obtain solution 5, 5ml of 1mol / L CTAB was added to solution 5, mixed and stirred for 2h, and then 0.35g of metal oxide TiO2 was added, mixed and ball-milled for 2h to obtain coating slurry 6.
[0144] Then, 0.8L of 2mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1.5) and 250ml of 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) were stirred for 3h at 25°C and pH 11 to obtain solution 7. Solution 7 was added to the coating slurry 6 and stirred for 30min to obtain mixed slurry 8. Then, the mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 220°C for 8 hours. Then, it was reduced at 380°C (heating rate of 12°C / min) for 7 hours in a 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst Cat-5. The content of active precious metal components is 0.21% by weight, the particle size of active precious metal components is between 2.6-2.8nm, the particle size of coating is between 80-150nm, the mesopore size distribution is 2-5nm, and the specific surface area is about 400m 2 / g, and the powder loss rate of the coating is 0.2%.
[0145] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 295℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0146] Example 6
[0147] This example is used to illustrate the monolithic catalyst and its preparation method and application according to the present invention.
[0148] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 1 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0149] Secondly, 3.6g of isopropanol and 0.368g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.012ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 1g of commercially available TS-1 seed crystals and 0.5g of P123 at 40°C for 1h to obtain solution 5, 5ml of 1mol / L CTAB was added to solution 5, mixed and stirred for 2h, and then 0.35g of metal oxide TiO2 was added, mixed and ball-milled for 2h to obtain coating slurry 6.
[0150] Then, 1L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 2:1) and 180ml of 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) were stirred at 25°C and pH 12 for 3h to obtain solution 7. Solution 7 was added to the coating slurry 6 and stirred for 30min to obtain mixed slurry 8. Then, the mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 250°C for 5 hours. Then, it was reduced at 360°C (heating rate of 15°C / min) for 10 hours in a 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst Cat-6. The content of active precious metal components is 0.24% by weight, the particle size of active precious metal components is between 2.1-2.2nm, the particle size of coating is between 80-150nm, the mesopore size distribution is 2-5nm, and the specific surface area is about 400m 2 / g, and the powder loss rate of the coating is 1%.
[0151] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 275℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 450h (i.e., the reaction was carried out continuously for 450h, and the catalytic activity of the catalyst did not decrease significantly).
[0152] Example 7
[0153] This example is used to illustrate the monolithic catalyst and its preparation method and application according to the present invention.
[0154] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0155] Secondly, 3.6g of isopropanol and 0.368g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.1ml / min and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 1g of commercially available TS-1 seed crystals and 0.5g of P123 at 40°C for 1h to obtain solution 5, 5ml of 1mol / L CTAB was added to solution 5, mixed and stirred for 2h, and then 0.35g of metal oxide TiO2 was added, mixed and ball-milled for 2h to obtain coating slurry 6.
[0156] Then, 0.7L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:2) and 240ml of 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) were stirred at 25°C and pH 9 for 3h to obtain solution 7. Solution 7 was added to the coating slurry 6 and stirred for 30min to obtain mixed slurry 8. Then, the mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 280°C for 4 hours. Then, it was reduced at 320°C (heating rate of 18°C / min) for 9 hours in a 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst Cat-7. The content of active precious metal components is 0.16% by weight, the particle size of active precious metal components is between 2.1-2.2nm, the particle size of coating is between 80-150nm, the mesopore size distribution is 2-5nm, and the specific surface area is about 400m 2 / g, and the powder loss rate of the coating is 0.2%.
[0157] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1, reaction pressure 0.1MPa, reaction temperature 320℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 400h (i.e., the reaction was carried out continuously for 400h, and the catalytic activity of the catalyst did not decrease significantly).
[0158] Example 8
[0159] This example is used to illustrate the monolithic catalyst and its preparation method and application according to the present invention.
[0160] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0161] Secondly, 3.6g of isopropanol and 0.368g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.015ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 1 hour, and then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 1g of commercially available TS-1 seed crystals and 0.5g of P123 at 40°C for 1h to obtain solution 5, 5ml of 1mol / L CTAB was added to solution 5, mixed and stirred for 2h, and then 0.35g of metal oxide TiO2 was added, mixed and ball-milled for 2h to obtain coating slurry 6.
[0162] Then, 0.6L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 150ml of 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) were stirred at 25°C and pH 10 for 3h to obtain solution 7. Solution 7 was added to the coating slurry 6 and stirred for 30min to obtain mixed slurry 8. Then, the mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 300°C for 4 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst Cat-8. The content of active precious metal components is 0.14% by weight, the particle size of active precious metal components is between 2.8-3.0nm, the particle size of coating is between 300-400nm, the mesopore size distribution is 15-30nm, and the specific surface area is about 200m2 / g, and the powder loss rate of the coating is 0.5%.
[0163] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 350℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 420h (i.e., the reaction was carried out continuously for 420h, and the catalytic activity of the catalyst did not decrease significantly).
[0164] Example 9
[0165] This example is used to illustrate the monolithic catalyst and its preparation method and application according to the present invention.
[0166] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0167] Secondly, 3.6g of isopropanol and 0.368g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01ml / min and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, then heated to 90°C at a heating rate of 7-9°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 1g of commercially available TS-1 seed crystals and 0.5g of P123 at 40°C for 1h to obtain solution 5, 5ml of 1mol / L CTAB was added to solution 5, mixed and stirred for 2h, and then 0.35g of metal oxide TiO2 was added, mixed and ball-milled for 2h to obtain coating slurry 6.
[0168] Then, 0.7L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 220ml of 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 2:1) were stirred for 3h at 25°C and pH 10 to obtain solution 7. Solution 7 was added to the coating slurry 6 and stirred for 30min to obtain mixed slurry 8. Then, the mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 240°C for 7 hours. Then, it was reduced at 410°C (heating rate of 5°C / min) for 4 hours in a 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst Cat-9. The content of active precious metal components is 0.17% by weight, the particle size of active precious metal components is between 2.6-2.7nm, the particle size of coating is between 300-500nm, the mesopore size distribution is 10-50nm, and the specific surface area is about 300m 2 / g, and the powder loss rate of the coating is 0.6%.
[0169] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 300℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 450h (i.e., the reaction was carried out continuously for 450h, and the catalytic activity of the catalyst did not decrease significantly).
[0170] Example 10
[0171] This example is used to illustrate the monolithic catalyst and its preparation method and application according to the present invention.
[0172] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0173] Secondly, 3.6g of isopropanol and 0.368g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01ml / min and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 1g of commercially available TS-1 seed crystals and 0.5g of P123 at 40°C for 1h to obtain solution 5, 5ml of 1mol / L CTAB was added to solution 5, mixed and stirred for 2h, and then 0.35g of metal oxide TiO2 was added, mixed and ball-milled for 2h to obtain coating slurry 6.
[0174] Then, 0.9L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 250ml0.5mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:2) were stirred at 25°C and pH 11 for 3h to obtain solution 7. Solution 7 was added to the coating slurry 6 and stirred for 30min to obtain mixed slurry 8. Then, the mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 260°C for 5 hours. Then, it was reduced at 440°C (heating rate of 3°C / min) for 2 hours in a 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst Cat-10. The content of active precious metal components is 0.23% by weight, the particle size of active precious metal components is between 2.1-2.2nm, the particle size of coating is between 80-150nm, the mesopore size distribution is 2-5nm, and the specific surface area is about 400m 2 / g, and the powder loss rate of the coating is 0.2%.
[0175] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 285℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 450h (i.e., the reaction was carried out continuously for 450h, and the catalytic activity of the catalyst did not decrease significantly).
[0176] Comparative Example 1
[0177] An integral catalyst was prepared according to the method of Example 1, except that the cordierite honeycomb ceramic was not subjected to acid treatment, and the mixed slurry was directly added dropwise to the cordierite honeycomb ceramic that had not been treated with acid, thereby obtaining an integral catalyst Cat-D1, wherein the content of active precious metal components was 0.13% by weight, the particle size of the active precious metal components was between 3.5-4.5 nm, the particle size of the coating was between 80-150 nm, and the powder loss rate of the coating was 4.9%.
[0178] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 265℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that the CO concentration was about 1000ppm, the VOCs concentration was about 280ppm, the conversion rate was 96.8%, and the catalyst stability was 45h.
[0179] Comparative Example 2
[0180] Based on Example 1, the difference is that the coating slurry is prepared according to the following process:
[0181] 50g of TS-1 molecular sieve (purchased from Shanghai Zhuoyue Chemical Technology Co., Ltd., Na type, with a micropore pore size distribution of 0.5-0.65nm) was mixed with 100 grams of deionized water, and wet ball milling was used to obtain a molecular sieve slurry. Take 0.5L 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum palladium molar ratio of 1:1) and 200ml1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium lanthanum molar ratio of 1:1) and stir for 3h at 25°C and pH 9 to obtain a mixed solution. The mixed solution was added to the molecular sieve slurry and stirred for 30min to obtain a coating slurry. Then, the coating slurry was added dropwise to the acid-treated cordierite honeycomb ceramic, purged, dried, calcined, and reduced in sequence to obtain a monolithic catalyst Cat-D2. The content of the active precious metal component is 0.14% by weight, the particle size of the active precious metal component is between 4.5-5 nm, the particle size of the coating is between 80-150 nm, and the powder loss rate of the coating is 3.1%.
[0182] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 275℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO concentration was about 840ppm, VOCs concentration was about 220ppm, conversion rate was 97.6%, and catalyst stability was 100h.
[0183] It can be seen from the above examples and comparative examples that the monolithic catalyst prepared in the present invention exhibits a good catalytic effect in the process of catalytic oxidation of carbon-based oxygen-containing molecular gases, and the catalyst has significantly better stability and is suitable for continuous long-term operation.
[0184] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A monolithic catalyst, characterized in that: The monolithic catalyst comprises: A carrier, wherein the carrier is a regular carrier treated with acid; a coating layer attached to the carrier, the coating layer comprising titanium silicon molecular sieve and metal oxide; and an active component dispersed in the coating, the active component comprising a noble metal and optionally an alloying metal; The powder loss rate of the coating is less than 1%, preferably 0.1-1%; the particle size of the active component is 2-3nm.
2. The monolithic catalyst according to claim 1, characterized in that The particle size of the coating is 50-500nm; Preferably, the mesoporous channel size of the coating is 1-50 nm, and the specific surface area is 300-600 m 2 / g.
3. The monolithic catalyst according to claim 1 or 2, characterized in that: Relative to 100 parts by weight of the carrier, the content of the coating layer is 1-10 parts by weight, and the content of the active component is 0.1-1 part by weight.
4. The monolithic catalyst according to claim 1, characterized in that The structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
5. The monolithic catalyst according to any one of claims 1 to 4, characterized in that In the coating, the weight ratio of the titanium silicon molecular sieve to the metal oxide is 1:0.1-0.5; Preferably, the titanium silicate molecular sieve is TS-1 molecular sieve; Preferably, the metal oxide is selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2.
6. The monolithic catalyst according to any one of claims 1 to 5, characterized in that In the active component, the molar ratio of the noble metal to the alloy metal is 1:0.1-0.
3.
7. The monolithic catalyst according to claim 1 or 6, characterized in that: The noble metal is at least one of silver, ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably a combination of platinum and palladium.
8. The monolithic catalyst according to claim 1 or 6, characterized in that: The alloy metal is at least one of Fe, La and Ce, and is preferably a combination of La and Ce.
9. A method for preparing a monolithic catalyst, characterized in that: The method comprises the following steps: (1) treating the structured support with acid; (2) mixing an alcohol solution of a titanium source with an aqueous solution containing a microporous template and a silicon source, aging, removing alcohol, and then mixing the obtained gel solution with titanium silicon molecular sieve seed crystals and a mesoporous template; (3) mixing the mixed solution obtained in step (2) with the metal oxide and ball milling to obtain a coating slurry; (4) The coating slurry is mixed with a mixed solution containing a noble metal precursor and an optional structural additive, and the obtained mixed slurry is added to the acid-treated structured support, followed by purging, drying, calcining and reducing in sequence.
10. The method according to claim 9, characterized in that In step (1), the acid treatment process includes: using an acidic solution to reflux the structured carrier, then washing it to neutrality and drying it; Preferably, the concentration of the acidic solution is 1-3 mol / L; Preferably, the acid in the acidic solution is at least one of nitric acid, sulfuric acid and hydrochloric acid; Preferably, the conditions of the reflux treatment include: a temperature of 70-90° C. and a time of 12-36 hours; Preferably, the structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
11. The method according to claim 9, characterized in that In step (2), the specific process of mixing the alcohol solution of the titanium source with the aqueous solution containing the microporous template and the silicon source is: adding the alcohol solution of the titanium source to the aqueous solution containing the microporous template and the silicon source at a rate of 0.005-0.015 mL / min, stirring and mixing for 2-5 hours; Preferably, the titanium source is selected from at least one of tetraalkoxytitanium, tetraalkyl titanate and titanium tetrachloride; Preferably, the microporous template agent is selected from at least one of tetrapropylammonium hydroxide, tetrapropylammonium bromide and tetraethylammonium hydroxide; Preferably, the silicon source is selected from at least one of silicate, silicic acid, silica hydrogel and tetraethyl orthosilicate; Preferably, the titanium silicon molecular sieve seed crystal is a TS-1 molecular sieve seed crystal; Preferably, the mesoporous template agent is selected from at least one of P123, CTAB and n-butylamine.
12. The method according to claim 9, characterized in that In step (3), the metal oxide is selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2.
13. The method according to claim 9, characterized in that In step (4), the pH value of the mixed solution containing the noble metal precursor and the structural additive is 9-12; Preferably, the noble metal precursor is selected from at least one of chloroplatinic acid, hexahydroxoplatinic acid (IV) 2-hydroxyethylamine salt, platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate; Preferably, the structural additive is selected from at least one of ferric nitrate, cerium nitrate, lanthanum nitrate, lanthanum sulfate, lanthanum chloride, cerium sulfate and cerium trioxide.
14. The method according to claim 9 or 13, characterized in that: In step (4), the purging process is performed by using an air knife purging at 1.5-2.5 MPa; Preferably, the calcination conditions include: a temperature of 200-300° C. and a time of 4-10 hours; Preferably, during the reduction process, the reducing atmosphere is H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, and a mixed atmosphere of different CO concentrations; Preferably, the reduction conditions include: catalyst heating rate of 2-20°C / min, reduction temperature of 300-450°C, and reduction time of 1-10h.
15. A monolithic catalyst prepared by the method according to any one of claims 9 to 14.
16. Use of the monolithic catalyst according to any one of claims 1 to 8 and 15 in catalytic oxidation of carbon-based oxygen-containing molecular gases.
Citation Information
Patent Citations
Preparation method of ZSM-5 molecular sieve nanosphere with multi-level pore hollow structure
CN102689911A
Macroporous-microporous molecular sieve catalyst TS-1 preparation method
CN107720771A
High-silicon composite molecular sieve adsorbent for removing VOCs and preparation method of high-silicon composite molecular sieve adsorbent
CN111408342A
Method for preparing monolithic catalyst for purification of diesel exhaust
CN101797518A
Honeycomb-ceramic-type monolithic catalyst, and preparation method and application thereof
CN102133537A